2007
DOI: 10.1159/000099144
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration among Long-Term Care Elderly Patients with Oropharyngeal Dysphagia

Abstract: Introduction: Long-term care (LTC) residents, especially the orally fed with dysphagia, are prone to dehydration. The clinical consequences of dehydration are critical. The validity of the common laboratory parameters of hydration status is far from being absolute, especially so in the elderly. However, combinations of these indices are more reliable. Objective: Assessment of hydration status among elderly LTC residents with oropharyngeal dysphagia. Methods: A total of 28 orally fed patients with grade-2 feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 32 publications
1
71
1
2
Order By: Relevance
“…BUN and Cr results were recorded and a BUN/Cr ratio calculated. A BUN/Cr ratio of >20 was used as the cut-off for dehydration in the current study as is commonly reported in the dysphagia literature [9,4,22,23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BUN and Cr results were recorded and a BUN/Cr ratio calculated. A BUN/Cr ratio of >20 was used as the cut-off for dehydration in the current study as is commonly reported in the dysphagia literature [9,4,22,23].…”
Section: Methodsmentioning
confidence: 99%
“…The literature has demonstrated that, especially if reliant on oral intake alone, individuals with dysphagia following stroke often present with inadequate fluid intake [6][7][8] and dehydration [9].Therefore much of the research regarding fluid intake and hydration in the stroke population has involved patients presenting with dysphagia. One study comparing the fluid intake of hospitalized patients post-stroke with and without dysphagia found those without dysphagia permitted thin liquids drank significantly more than those with dysphagia prescribed thickened liquids (mean of 1237ml and 947ml, respectively), although only one patient from the total sample of patients met the minimum standard of fluid intake set at 1500ml [10].…”
Section: Introductionmentioning
confidence: 99%
“…The specific index used was the blood urea nitrogen/creatinine ratio (BUN/Cr). A conservative cut-off point for the ratio of greater than 20 was used to classify a participant as dehydrated, in keeping with previous studies of fluid intake and dehydration in the dysphagia population [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Of the seven participants, only one participant was well hydrated following a 24-hour consumption of thickened liquids, four participants had mild dehydration, and two participants had significant dehydration. According to Leibovitz and colleagues [31], individuals with dysphagia are at an elevated risk for dehydration. Given the participants in this study were healthy individuals and displayed signs of dehydration after only 24 hours, it is suggested that individuals with dysphagia on a thickened liquid diet for more than 24 hours are at a significant risk for dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Given the participants in this study were healthy individuals and displayed signs of dehydration after only 24 hours, it is suggested that individuals with dysphagia on a thickened liquid diet for more than 24 hours are at a significant risk for dehydration. Dehydration can lead to many negative health conditions including deterioration of cognitive status, changes in drug effects, poor wound healing, pressure sores, urinary tract infections, altered cardiac function, lethargy, weakness, constipation, and acute renal failure [31][32][33].…”
Section: Discussionmentioning
confidence: 99%